2016
DOI: 10.1161/circep.115.003197
|View full text |Cite
|
Sign up to set email alerts
|

PANCR, the PITX2 Adjacent Noncoding RNA, Is Expressed in Human Left Atria and Regulates PITX2c Expression

Abstract: Background Genome-wide studies reveal that genetic variants at chromosome 4q25 constitute the strongest locus associated with atrial fibrillation (AF), the most frequent arrhythmia. However, the mechanisms underlying this association are unknown. Our goal is to find and characterize left atrial expressed transcripts in the chromosome 4q25 AF risk locus that may play a role in AF pathogenesis. Methods and Results RNA sequencing performed on human left/right pairs identified an intergenic long noncoding RNA (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…A positive correlation of hypermethylated gene body with an increased gene expression has been reported by several groups [4547]. One might infer that PANCR expression is elevated as well as PITX2c ; besides, a positive correlation of expression was observed in human adult left atria tissue [30]. …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A positive correlation of hypermethylated gene body with an increased gene expression has been reported by several groups [4547]. One might infer that PANCR expression is elevated as well as PITX2c ; besides, a positive correlation of expression was observed in human adult left atria tissue [30]. …”
Section: Discussionmentioning
confidence: 70%
“…This gene is referred to as PANCR ( PITX2 adjacent noncoding RNA) and is expressed mainly in the left atrium of the human heart. Functionally, it has been suggested that PANCR co-regulates PITX2c expression during cardiomyocyte differentiation [30]. Because of numerous known functions of lncRNA in a range of cellular processes, dysregulation of lncRNAs not surprisingly has been identified as a hallmark in various benign and malignant diseases including BTC (for review see ref.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 On the basis of these insights and the impact of gene variants on chromosome 4q25 for AF, the genetic predisposition to AF has been identified as a promising candidate to develop personalized approaches to AF management. 10 In this issue of Circulation Arrhythmia and Electrophysiology, Gore-Panter et al 11 describe a new regulator of PITX2c expression in the left atrium: They identified a long noncoding RNA adjacent to the PITX2 gene (Pitx2 adjacent noncoding RNA [PANCR]). PANCR positively correlates with PITX2c mRNA expression in human patient left atrial appendage samples and knock down of PANCR in H9-derived cardiomyocytes depletes cells of PITX2c.…”
Section: See Article By Gore-panter Et Almentioning
confidence: 99%
“…12,13 But is this really surprising? All tissue samples available to Gore-Panter et al 11 -similar to what is available to other research groups-were obtained from patients requiring open-heart surgery for severe heart disease (usually coronary artery bypass grafting and valve surgery). It is entirely unknown how atrial PITX2 (and PANCR) expression is altered by pressure overload, diabetes mellitus, hypoxia/ischemia, inflammation, autonomic dysfunction, or by the stress of open-heart surgery.…”
Section: See Article By Gore-panter Et Almentioning
confidence: 99%
See 1 more Smart Citation